Studi Kesiapan Pengguna Dalam Implementasi Mobile Health untuk Monitoring Pelayanan Kehamilan - Sandra Hakiem Afrizal (Lembaga Penerbitan Universitas Esa Unggul, 2020)
AbstractNowadays, Personal Health Record (PHR) implementation in developing country has proven to improve the quality of care as well as patient empowerment. Since women in reproductive age has been noticed as frequent user of social media, internet and mobile applications, so that the pregnant patient seems to be a potential user of mobile Pregnancy Monitoring System (mPMS). However, readiness towards the mHealth implementation amongst women during antenatal period is less known. The aim of this study is to describe readiness towards a mobile pregnancy monitoring system implementation from the perspectives of pregnant mother. A qualitative study using in-depth interview was conducted during antenatal care (ANC) visit in a Primary Health Care of South Tangerang District, an urban area in Banten Province-Indonesia. Seven informants including pregnant women from first, second, and third trimester were purposively recruited. The interview was audiotape, transcribed verbatim and analyzed using thematic analysis. Pregnant women showed their attention in the use of mHealth for antenatal monitoring. However, some barriers such as lack of technology capability, lack of trust to technology, poor internet access were found and may lead them to be inadequately ready to adopt mHealth for antenatal care. As conclusions, this study has described the mHealth readiness and identified potential barriers toward the mHealth implementation amongst user.Keywords: readiness, mobile pregnancy monitoring system, mobile health, antenatal care, primary health care AbstrakPelaksanaan Personal Health Record (PHR) di negara berkembang terbukti mampu meningkatkan kualitas pelayanan serta meningkatkan peran pengguna untuk melakukan pengawasan secara individu. Penelitian terdahulu menyimpulkan bahawa Wanita di usia reproduktif dianggap sebagai pengguna media sosial, internet, dan aplikasi selule yang aktif, sehingga ibu hamil sangat berpotensi untuk menggunakan suatu Sistem Pemantauan Kehamilan berbasis mobile. Saat ini kesiapan terhadap implementasi mHealth di kalangan wanita yang terlibat dalam proses antenatal di layanan primer seperti Puskesmas masih belum banyak diteliti. Tujuan dari penelitian ini adalah untuk menggali kesiapan penerapan sistem pemantauan kehamilan berbasis mobile dari perspektif pengguna yang terlibat dalam proses pelayanan antenatal di Puskesmas. Penelitian kualitatif dengan wawancara mendalam dilakukan pada saat kunjungan antenatal care (ANC) di Puskesmas Kota Tangerang Selatan, di Provinsi Banten-Indonesia. Tujuh informan termasuk ibu hamil trimester I, II, dan III dipilih secara purposif. Hasil analisis menunjukkan bahwa ibu hamil di wilayah Kota Tangerang Selatan umumnya telah siap dalam penggunaan mHealth beberapa faktor yang mempengaruhi kesiapan tersebut diantaranya adalah faktor sosial seperti individu dan dukungan lingkungan, serta faktor teknikal. Sebagai kesimpulan, penelitian ini telah mendeskripsikan kesiapan implementasi mHealth dalam pelayanan antenatal dan mengidentifikasi potensi hambatan dalam implementasi mHealth.Kata Kunci: kesiapan, sistem monitoring pelayanan ibu hamil, mobile health, antenatal care, puskesmas